The Influence of Net Profit Margin and Debt to Equity Ratio on Company Value in the Cement Sub-Sector on the Indonesian Stock Exchange - Saepudin, Asep; Rinandiyana, Lucky Radi (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Increasing the value of the company is an achievement, that is following the wishes of the owners because as the value of the company increases, the welfare of the owners will also increase. This research aims to analyze and test how much influence Net Profit Margin (NPM) and Debt to debt-to-equity ratio (DER) have on Company Value. This research uses secondary data presented on IDX. The sample used in this research is the Cement Sub Sector Companies Listed on the Indonesia Stock Exchange for the 2018-2022 Period which are listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. The analytical method used is multiple linear analysis. The research results show that Net Profit Margin (NPM) partially has a negative effect on Company Value. Meanwhile, Debt to Equity Ratio (DER) has a positive effect on Company Value. Simultaneously Net Profit Margin (NPM) and Debt to debt-to-equity ratio (DER) have a significant effect on Company Value. This is because several other indicators influence Company Value.